How much of these hills is gold - Zhang, C Pam (Riverhead Books, 2020)
Newly orphaned children of immigrants, Lucy and Sam are suddenly alone in a land that refutes their existence. Fleeing the threats of their western mining town, they set off to bury their father in the only way that will set them free from their past. Along the way, they encounter giant buffalo bones, tiger paw prints, and the specters of a ravaged landscape as well as family secrets, sibling rivalry, and glimpses of a different kind of future.